Nanoindentation studies on single crystals of Zn-Mg-Er and Zn-Mg-Ho icosahedral phases - Mukhopadhyay N.K.; Belger A.; Paufler P.; Uhrig E.; Brühne S.; Assmus W. (My University, 2025)
Single crystals of Zn-Mg-Er and Zn-Mg-Ho icosahedral phases were grown from the melt using the liquid encapsulated top seeded solution growth technique. The fivefold planes of these as-grown single crystals were polished and used for the present nanoindentation studies using Hysitron triboscope attached to an atomic force microscope with a maximum load up to 16 mN. The reduced Young's modulus (Er) and nanohardness (H) were found to be 135 ± 10 GPa and 8.5 ± 0.2 GPa for the F-type Zn65Mg25Er10 quasicrystal whereas for the P-type Zn74Mg15Ho11 quasicrystal (QC) these were 135 ± 10 GPa and 7.8 ± 0.2 GPa, respectively. Using the appropriate constants, the average E in both the quasicrystalline alloys was estimated as 140 ± 10 GPa. The elastic and plastic deformation characteristics in load-displacement, F-h, curve appears to be identical in both the QC phases. The peculiarity in the load-displacement curves, in terms of pop-ins were observed frequently. AFM images showed the steps in the pile-up material which can be identified as shear bands and correlated with the pop-ins. The first pop-in was observed in the load range of 70 μN in case Zn-Mg-Ho and 84 μN in case of Zn-Mg-Er QC. The contact pressure, p, turns out to be 13 GPa for Zn-Mg-Ho and 18 GPa for Zn-Mg-Er QC. The maximum shear stress under the indent, τTresca is found to vary from 6 to 8 GPa, which is close to the theoretical shear strength of this material (∼E/20). The energy required for the indentation was determined from the first pop-ins and it turned out to be 0.88 eV/atom, close to the thermal energy required for deformation of quasicrystals. Thus the 'pop-ins' are attributed to the elastic-plastic transition during indentation. © 2007 Elsevier B.V. All rights reserved.